The Determinant of Regional Expenditure: A Study in Central Java - Bagas Prasetyo; Winny Perwithosuci (www.amertainstitute.com, 2023)
Regional expenditures are part of regional spending, where these expenditures consist of direct expenditures and indirect expenditures. This studyaims to examine the factors that influence regional expenditures. Variables that affect regional spending consist of Regional Original Income, Gross Regional Domestic Product, Human Development Index, and Population. This research method uses panel data regression with the Fixed Effect Model approach throughEviews 10 to analyze panel data from 2015-2020 in 29 districts and six cities in Central Java province. The study results show that Regional Original Income andGross Regional Domestic Product significantly positively affect Regional expenditure. In contrast, the Human Development Index and Total Population have no significant effect on Regional expenditure.